The Next Supreme Leader Succession in the Islamic Republic of Iran - Nader, Alireza (RAND Corporation, 2011)
As the commander in chief and highest political authority in Iran, the current Supreme Leader, Ayatollah Ali Khamenei, has played a critical role in the direction of the Islamic Republic of Iran. This monograph identifies three key factors that will shape succession of the next Supreme Leader and outlines five alternative scenarios for the post-Khamenei era. It situates all of this within the context of the June 2009 election.